Influence of core halogenation on the electronic structure of naphthothiadiazole derivatives - Ajdari, Mohsen; Landwehr, Felix; Hoffmann, Marvin; Hoffmann, Hendrik; Bunz, Uwe H. F.; Dreuw, Andreas; Tegeder, Petra (The journal of physical chemistry. C, Energy, materials, and catalysis, 2021)
Naphthothiadiazoles are promising electron acceptors for applications in organic semiconductor-based (opto)electronic devices. Here, we studied the structural and electronic properties of naphthothiadiazole (NTD) derivatives adsorbed on Au(111) in the monolayer and thin films using temperature-programmed desorption as well as vibrational and electronic high-resolution electron energy loss spectroscopy. In addition, we performed state-of-the-art quantum chemical calculations to further illuminate electronic properties. In the monolayer and multilayer coverage regime, the NTD derivatives adsorbed in a planar fashion with the molecular backbone oriented parallel to the gold surface. Several singlet and the first triplet transition energies are determined. The optical gap (S0 → S1 transition) in the nonhalogenated parent NTD is found to be 2.6 eV, whereas it is reduced by 200 meV in the chlorinated and brominated NTD. All experimentally observed singlet and triplet transition energies are reduced due to halogenation, which is underlined by theory.
Gesehen am 05.05.2021